2019
DOI: 10.1088/1755-1315/343/1/012145
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of moringa leaf (Moringa oleifera L.) extract against the growth of Staphylococcus epidermidis

Abstract: The study was aimed to determine the antimicrobial activity of Moringa oleifera L. leaf extract againts the growth of Staphylococcus epidermidis. This study was conducted at the Microbiology Laboratory of the Department of Pharmacy, Ministry of Health Polytechnic Makassar, South Sulawesi. Three different concentrations of Moringa leaf extract were used, namely 2% b/v, 4% b/v and 8% b/v which were tested on S. epidermidis bacteria using the paper disk diffusion method. The results showed that Moringa oleifera L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Several investigations suggested that Moringa oleifera Lam. acts as an antibacterial agent on Gram-negative and Gram-positive bacteria [ 13 , 14 , 15 ]. M. oleifera Lam.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations suggested that Moringa oleifera Lam. acts as an antibacterial agent on Gram-negative and Gram-positive bacteria [ 13 , 14 , 15 ]. M. oleifera Lam.…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenols undermine the structural integrity of the cell membrane by interacting with the proteins and enzymes there, lowering cell activity, and finally, killing microorganisms (Mostafa et al., 2018 ). Higher extract concentrations were shown to dramatically alter the moringa leaves' dose‐dependent antibacterial activity against Staphylococcus epidermis (Abadallah & Ali, 2019 ; Mursyid et al., 2019 ). The effects of extracts from the leaves of Matricaria recutita and M. oleifera on 40 susceptible and antibiotic‐resistant bacterial strains were examined by Atef et al.…”
Section: Medicinal Propertiesmentioning
confidence: 99%
“… 8 Moringa leaves extract at 8% weight per volume (w/v) can inhibit the growth of Staphylococcus epidermidis with an inhibition zone around 14 mm. 9 …”
Section: Introductionmentioning
confidence: 99%